Guidance And Assistance In Repair Of Centrifuge Laboratory Equipment Based On Standards Of Centrifuge Motor Speed Data In Turi Health Centre, Lamongan Regency, East Java - I Dewa Gede Hari Wisana; Her Gumiwang Ariswati; Sumber Sumber; Levana Forra Wakidi (Frontiers in Community Service and Empowerment, 2022)
One of the equipment in the Turi Health Center laboratory is a Centrifuge. The problem at the Turi Health Center with the centrifuge is that this centrifuge has a large usage load of 8-10 hours per day, without having electromedical personnel. In this Centrifuge, it is often found that the cleanliness of the tools is not good, the placement of the tools is inadequate, the electrical installation network is not standard (Grounding) and the maintenance and maintenance is lacking, there is no regular calibration so there is no certainty of the accuracy of the results obtained. As a result of the impact obtained is a tool that is not suitable for use, the tool is quickly damaged which can harm the diagnosis of patients. Community Service Activities with the implementation team from Poltekkes Kemenkes Surabaya working together as partners in this activity aims to carry out repairs according to Centrifuge standards and provide knowledge and skills about simple maintenance and repairs on Centrifuges Correctly. The first stage in providing solutions to problems faced by the Turi Health Center is to conduct a study through Focus Group Discuss (FGD). The second stage is compiling a user manual. The third stage is the implementation of mentoring and counseling on centrifuge repair using a maintenance and repair manual. And the fourth stage is the implementation of centrifuge repair by providing opportunities for laboratory personnel, Medical and non-medical personnel to be able to independently carry out simple repairs and to know important indicators in the event of damage. The output target of the community service carried out is a simple repair guide book for centrifuge equipment so that later laboratory equipment at the Turi Health Center, especially the Centrifuge, can work according to the Centrifuge Motor Speed Standard.